Integrasi Kurikulum Pada Sekolah Adiwiyata - Mahdi, Ahmad; Erihadiana, Mohamad; Ruswandi, Uus (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2023)
Curriculum according to wikipedia Indonesian is a set of subjects and educational programs provided by an educational institution that contains lesson designs that will be given to lesson participants in one period of education. Etymologically, curriculum comes from English, namely the word curriculum which means lesson plan (Echolz:1984). The word Curriculum itself comes from the word